Loneliness and Healthcare Use in Older Adults: Evidence From a Nationally Representative Cohort in Northern Ireland—A Cross-Sectional Replication Study - Burns, Annette; Leavey, Gerard; O'Sullivan, Roger (Frontiers in Public Health, 2021)
Background: Few have explored associations between loneliness and healthcare use independent of health and health behaviours. Recent indication of gender effects also requires validation across health service and cultural settings. We investigated the associations among loneliness, health and healthcare use (HCU) in older adults including stratification to investigate whether associations differed by gender. Methods: Secondary analysis of a nationally representative sample of 8,309 community-dwelling adults aged 50 and over from the Northern Ireland Cohort for the Longitudinal Study of Ageing. Primary outcomes were: self-reported General Practice (GP) and emergency department (ED) visits in past year. Negative binomial and logistic regression analysis were used to investigate associations between loneliness and HCU, later adjusting for potential confounders (health and health behaviours). Results: Loneliness was consistently positively associated with both GP and ED visits (with IRRs ranging from 1.10-1.49 for GP visits, 1.16-1.98 for ED visits and ORs ranging from 1.13-1.51 for reporting at least one ED visit). With addition of health and health behaviours, all associations between loneliness and HCU became non-significant, excepting a small independent association between UCLA score and GP visits (IRR 1.03 (95% CI 1.01-1.05)). Stratification of models revealed no gender effects. Conclusion: All but one association between loneliness and HCU became nonsignificant when health and health behaviours were included. The remaining association was small but implications remain for health service resources at population level. No gender effects were present in contrast to recent findings in the Republic of Ireland. Further studies on gender, loneliness and healthcare use needed.